Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Construction of the CRISPR/Cas12a-digital integrated immunoassay technology for CD44 detection - Songbai Tian; Xin Tang; Saijun Zhang; Yuexin Yao; Ran Bi; Haixia Li; Xiaoming Sun; Zhuo Chen (Analytica Chimica Acta, 2026)

Macrophage-targeted dual-responsive hollow mesoporous silica nanosystem for photothermal and immunomodulatory elimination of intracellular MRSA - Qiao Guo; Yongchao Yao; Jipeng Xiao; Xinyu Lu; Yiyuan Pu; Ran Li; Zhuo Zhang; Penghai Tang; Yuchen Jiang; Jianbin Luo (Chemical Engineering Journal, 2026)

A chimeric PRRSV vaccine with dual Nsp2 deletions elicits cross-lineage protection against heterologous challenge - Zhuo-ran Miao; Bo Han; Ling-zhai Meng; Zhen-hui Ren; Yi-han Lu; Jing Li; Wen Sun; Shi-qin Zhang; Jia Wang; Jin-jin Ma; Jia-Lu Li; Yu-tong Zhu; et al. (The Veterinary Journal, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Emergence of a novel porcine reproductive and respiratory syndrome virus strain inducing biphasic temperature fluctuations in Tianjin, northern China - Jia Wang; Yi-Han Lu; Bo-Han; Hai-Tao Yang; Xin-lei Li; Wen Sun; Shi-Qin Zhang; Zhuo-Ran Miao; Xue-Jiao Cheng; Chun-Xue You; Ying-Feng Sun (Research in Veterinary Science, 2026)

From growth to decline: The dynamic effects of maize-based cropping systems on soil organic carbon storage in Northeast China - Jin-Sai Chen; Zhuo Shi; Yu-Gang Tian; Hao-Ran Li; Hong-Xuan Duan; Zhi-Heng Qin; Jia Cheng; Yash Pal Dang; Bai-Jian Lin; Xin Zhao; Hai-Lin Zhang (Agriculture, Ecosystems & Environment, 2025)

CCP domain containing protein from complement factor H of Paralichthys olivaceus has potential effects against Edwardsiella piscicida infection - Xuan-yue Wang; Yu-ting Du; Xin-yi Jiang; Zhuo-ran Ma; Chao-ran Zhang; Xue-peng Li; Zeng-zhi Yuan; Mo-fei Li (Aquaculture, 2025)

High urea promotes mitochondrial fission and functional impairments in astrocytes inducing anxiety-like behavior in chronic kidney disease mice - Xi Zhao; Shengyao Zhang; Mengna Wu; Binyun Zhang; Guoran Wan; Meng Zhang; Jing Li; Zhuo Fei; Guoqi Zhu; Shaoqiu Jiang; Mohan Xiao; Wanjia Liu; et al. (Metabolic Brain Disease, 2025)

Study on the dissolved inorganic carbon cycling and carbon emission during the wet season across cascade hydropower stations on the Jinsha River, southwestern China - Dan Zhang; Yufei Bao; Jingjie Feng; Yu Xu; Yuchun Wang; Ran Li; Yanliang Du; Zhuo Chen; Shanze Li; Jie Wen; Meng Sun (Gondwana Research, 2025)

The Arabidopsis heterotrimeric G protein α subunit binds to and inhibits the inward rectifying potassium channel KAT1 - Jiang-Fan Guo; Hui Zhou; Zhuo-Ran Hu; Ya-Lan Yang; Wen-Bin Wang; Yan-Ru Zhang; Xue Li; Nuerkaimaier Mulati; Ying-Xin Li; Lu Wu; Yu Long; Jun-Min He (Plant Science, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Coalescence characteristics of free-living and particle-attached bacteria in a cascade river-reservoir system: A case study of the Jinsha River - Dan Zhang; Yufei Bao; Yuchun Wang; Jingjie Feng; Ran Li; Yanliang Du; Dianchang Wang; Fei Chen; Shanze Li; Jie Wen; Zhuo Chen (Journal of Environmental Management, 2025)

Enhanced ultra-high efficiency in high-energy–density PbHfO3-based antiferroelectric ceramics through synergistic effect design - Jian Zhou; Deke Liu; Ruoxin Chen; Kai Zhang; Ruoqi Jin; Hongchen Sun; Yujun Feng; Xiaoyong Wei; Zhuo Xu; Ran Xu (Chemical Engineering Journal, 2024)

Three new glycosides from the stems of Eurya chinensis R. Br - Hui-Jun Liang; Qian-Ran Li; Bai-Lin Li; Chen Ni; Wei-Jie Zhang; Yu-Wen Fan; Zhuo-Yi Ao; Juan-Juan Hu; Jie Yuan; Jie-Wei Wu (Natural Product Research, 2024)

Changes in Accessibility of Chinese Coastal Ports to Arctic Ports under Melting Ice - Ran Zhang; Yi Zuo; Zhuo Sun; Shuang Cong (Journal of Marine Science and Engineering, 2023)
Global warming has accelerated the melting of Arctic sea ice, providing favorable conditions for Arctic shipping. Arctic ports are gaining prominence in shipping networks and international trade. Accessibility is a key indicator of port facilitation, and identifying trends in Arctic port accessibility holds significance for Arctic route planning and port development. To achieve this, this paper develops a modeling framework for assessing the accessibility of Arctic ports. First, we utilize the Coupled Model Intercomparison Project (CMIP6) model to predict sea ice conditions and quantify the navigation risk for open water (OW) vessels and Arc4 ice-class (Arc4) vessels during the summer months of 2030–2050. The A-star (A*) algorithm is then used to plan the vessel’s shortest route while avoiding high-risk waters. Finally, changes in the accessibility of Arctic ports are calculated by using an improved gravity model. The framework is applied for the quantitative analysis of the accessibility of Chinese coastal ports to Arctic ports. The results indicate that accessibility to Arctic ports will gradually increase for all Chinese ports in the future, with the port of Shanghai continuing to maintain its prominence under the trend of melting sea ice.

Effects of salinity on sulfur-dominated autotrophic denitrification microorganisms: Microbial community succession, key microorganisms and response mechanisms - Zhuo-Ran Li; Xue-Ning Zhang; Hong-Cheng Wang; Hao-Yi Cheng; Ai-Jie Wang; Yan-Qing Zhang; Chong-Wei Cui; Yi-Lu Sun (Chemical Engineering Journal, 2023)

Emerging roles of air pollution and meteorological factors in autoimmune eye diseases - Fan Cao; Zhuo-Ran Liu; Qin-Yu Ni; Chen-Kai Zha; Shu-Jie Zhang; Jia-Min Lu; Yue-Yang Xu; Li-Ming Tao; Zheng-Xuan Jiang; Hai-Feng Pan (Environmental Research, 2023)

Design and operation insights concerning a pilot-scale S0-driven autotrophic denitrification packed-bed process - Yi-Lu Sun; Zhuo-Ran Li; Xue-Ning Zhang; Heng Dong; Zhi-Min Qian; Shan Yi; Wei-Qin Zhuang; Hao-Yi Cheng; Ai-Jie Wang (Chemical Engineering Journal, 2023)

Field investigation on the change process of microbial community structure in large-deep reservoir during the initial impoundment - Sizhen Liang; Fangbo Zhang; Ran Li; Hailong Sun; Jingjie Feng; Zhuo Chen; Honghui Lin (Journal of Environmental Management, 2023)

Interaction network analysis revealed biomarkers in myocardial infarction - Tong Zhang; Li-Li Zhao; Zhuo-Ran Zhang; Pei-De Fu; Zhen-Dong Su; Li-Chun Qi; Xue-Qi Li; Yu-Mei Dong (Molecular Biology Reports, 2014)

The genetic mechanism of a translational landslide - Xuan-Mei Fan; Qiang Xu; Zhuo-Yuan Zhang; Dong-si Meng; Ran Tang (Bulletin of Engineering Geology and the Environment, 2009)

Evaluation of water quality in Er-longshan reservoir by fuzzy model - Ying Zhang; Chun-Hui Fan; Zhuo Diao; Xin-Ran Peng; Xin Bai (Interdisciplinary Sciences: Computational Life Sciences, 2009)